A novel biosensor based on intestinal 3D organoids for detecting the function of BCRP. (1st January 2017) - Zhang, Lei; Zhao, Junfang; Liang, Chenmeizi; Liu, Mingyao; Xu, Feng; Wang, Xin
Abstract: Breast cancer resistance protein (BCRP), a key drug efflux transporter, significantly affects the therapeutic efficacy of many drugs. Thus, screening specific BCRP inhibitors and distinguishing between substrates and non-substrates of BCRP are valuable in drug discovery and development. This study presents a novel BCRP biosensor based on intestinal 3D organoids for rapid and sensitive detection of BCRP function. First, the crypts were isolated from mouse small intestine, and cultured in advanced DMEM/F12 medium to develop intestinal 3D organoids. Second, immunohistochemical studies demonstrated that BCRP protein in the organoids presented a similar expression and physiologic position to the small intestinal epithelium. Finally, the cultured organoids were treated in BCRP fluorogenic probe substrate Hoechst 33342 with or without BCRP inhibitor Ko143 and YHO-13177. The fluorescence intensity of Hoechst 33342 released from inner of the organoids was detected by microplate reader and the concentrations were calculated. Ko143 and YHO-13177 significantly inhibited the BCRP-mediated Hoechst 33342 transport in the 3D organoids. Consequently, a rapid and efficient biosensor has been successfully established to study BCRP, especially screening BCRP inhibitors in a high-throughput way.